STUDY ON THE PREFERENCE OF SENIOR CITIZENS IN URBAN PARK PUBLIC FACILITIES - Huang, Tian; Huang, Chiwu (PEOPLE: International Journal of Social Sciences, 2019)
As aging has become one of the social trends in many countries and regions around the world, the urban park environment for senior citizens' activities and social places has become one of the concerns. This study explores the preferences of senior citizens for the use of public facilities in urban parks. Through six non-participatory observations of the use of public facilities in the park by the elderly in Taipei Daan Forest Park, Taiwan, it was found that the public facilities most used by the elderly in the park were seats, followed by green space, then Trails and gazebos, In addition, through the chi-square analysis, it is found that the gender distribution of the elderly users in the physical fitness facilities and the bird watching area is significantly different, the proportion of male users is higher than that of females, and the gender distribution of the elderly users in the green space active areas also exists significant difference, namely the proportion of female elderly users is higher than that of males. The study found that it can provide some reference for urban park planners, park planning departments and park managers.